The Influence of Word of Mouth, Product Quality, Price, and Lifestyle on Thrift Fashion Buying Decision - Andri Astuti Itasari; Dewi Maria Herawati; Maulia Hikmah (Mediakita, 2026)
Thrifting in Indonesia is becoming increasingly popular, with young people leading the trend. The government’s ban on the sale and purchase of thrifted clothing does not prevent consumers from continuing to use thrifted clothing, as they consider these products are good and the prices are affordable. Therefore, thrifted clothing has become a lifestyle among young people, including students. This research uses a quantitative, survey-based approach. Primary data was obtained from questionnaires, while secondary data was obtained from journals, books, and other documents. The population of this study was the students of SMK Wijaya Kusuma Surakarta, and the sample consisted of 100 respondents from the school. This study used logistic regression (binary logit) to determine which students bought and which did not buy thrifted clothing. The results showed that, individually, word of mouth had a significant effect of 0.010, product quality was 0.047, price was 0.033, and lifestyle was 0.009. The simultaneous test was 0.000, with a chi-square of 67.101.